2019
DOI: 10.1371/journal.pgen.1008332
|View full text |Cite
|
Sign up to set email alerts
|

Reshuffling yeast chromosomes with CRISPR/Cas9

Abstract: Genome engineering is a powerful approach to study how chromosomal architecture impacts phenotypes. However, quantifying the fitness impact of translocations independently from the confounding effect of base substitutions has so far remained challenging. We report a novel application of the CRISPR/Cas9 technology allowing to generate with high efficiency both uniquely targeted and multiple concomitant reciprocal translocations in the yeast genome. Targeted translocations are constructed by inducing two double-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 68 publications
2
61
0
Order By: Relevance
“…In all of these studies, multiple copies of Ty elements were found to be involved in the generation of translocations. In the study that employed CRISPR, similar multiple translocation events were observed (61). However, Ty elements in S. cerevisiae are distributed across the genome, unlike C. neoformans, where all of the Tcn2 elements are clustered in centromeres.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In all of these studies, multiple copies of Ty elements were found to be involved in the generation of translocations. In the study that employed CRISPR, similar multiple translocation events were observed (61). However, Ty elements in S. cerevisiae are distributed across the genome, unlike C. neoformans, where all of the Tcn2 elements are clustered in centromeres.…”
Section: Discussionmentioning
confidence: 62%
“…cerevisiae, where DSBs were generated with gamma radiation, HO-endonuclease, or CRISPR (60)(61)(62). In all of these studies, multiple copies of Ty elements were found to be involved in the generation of translocations.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of translocations in the phenotypic adaptation of yeast has been widely investigated by using genetically engineered strains (Tosato and Bruschi, 2015; Fleiss et al, 2019). However, the description of spontaneous chromosomal rearrangements in clonal populations is much less described.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of using CRISPR/Cas9 to engineer chromosome rearrangements in other model systems include the creation of an oncogenic translocation in mice (5), translocations in yeast (6), translocations and inversions in C. elegans (7,8), and inversions in zebrafish (9). This study represents the first report of a chromosomal rearrangement induced by CRISPR/Cas9 in the Drosophila germline.…”
Section: Introductionmentioning
confidence: 91%